Conceptualising language acquisition process in Content and Language Integrated Learning (CLIL) classroom context: a systematic review - Saturnus, Meridian; Ashadi, Ashadi; M. Zaenal Abidin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Researchers have highlighted that a critical component of language acquisition is the opportunity to learn in authentic contexts where natural teaching-learning scenarios can occur. Despite this, the Direct Method (DM) and the Grammar Translation Method (GTM) remain the predominant approaches in English schools. This systematic review, however, aimed to delve into the complexities of language acquisition in Content and Language Integrated Learning (CLIL) classrooms worldwide. Findings from the review reveal that instructional methods and teachers' proficiency play a crucial role in language learning success within CLIL settings. The results showed a strong case for continuing CLIL methods in educational methodology. Similarly, the research suggests that using CLIL allows both the teacher and students to acquire learning in a natural context, including developing cognitive skills.